How common is repetitive strain injury?. Issue 5 (4th December 2007) - Palmer, K T; Reading, I; Calnan, M; Coggon, D
Abstract : Objective: Statistics from Labour Force Surveys are widely quoted as evidence for the scale of occupational illness in Europe. However, occupational attribution depends on whether participants believe their health problem is caused or aggravated by work, and personal beliefs may be unreliable. The authors assessed the potential for error for work-associated arm pain. Methods: A questionnaire was emailed to working-aged adults, randomly chosen from five British general practices. They were asked about: occupational activities; mental health; self-rated health; arm pain; and beliefs about its causation. Those in work (n = 1769) were asked about activities likely to cause arm pain, from which the authors derived a variable for exposure to any "arm-straining" occupational activity. The authors estimated the relative risk (RR) from arm-straining activity, using a modified Cox model, and derived the population attributable fraction (PAF). They compared the proportion of arm pain cases reporting their symptom as caused or made worse by work with the calculated PAF, overall and for subsets defined by demographic and other characteristics. Results: Arm pain in the past year was more common in the 1143 subjects who reported exposure to arm-straining occupational activity (RR 1.2, 95% CI 1.1 to 1.5). In the study sample as a whole, 53.9% of 817 cases reported their arm pain as work-associated, whereas the PAF for arm-straining occupational activity was only 13.9%. The ratio of cases reported as work-related to the calculated attributable number was substantially higher below 50 years (5.4) than at older ages (3.0) and higher in those with worse self-rated and mental health. Conclusions: Counting people with arm pain which they believe to be work-related can overestimate the number of cases attributable to work substantially. This casts doubt on the validity of a major source of information used by European governments to evaluate their occupational health strategies.